User decision-making and technology choices in the U.S. carsharing market. (October 2016) - Zoepf, Stephen M.; Keith, David R.
Abstract: Each time a user of a carsharing service reserves a vehicle they choose from a selection of vehicles that vary in attributes including rental price, the distance of the vehicle from their current location, the availability of the vehicle at their desired reservation time, and the type of vehicle (e.g., gasoline, Hybrid, Plug-in Hybrid or Electric). In this paper we analyze the results of a discrete choice survey administered to members of a leading North American carsharing organization. We quantify how carsharing users value price, distance from them, schedule and vehicle type. We find that for an average user, traveling one mile for a vehicle or rescheduling a trip by up to one hour are each approximately equivalent to a US2/hour increase in vehicle price. We find that carsharing acts as a conduit to introduce users to new vehicle technology: more than half users report having driven a Hybrid vehicle through carsharing, representing 400 users exposed for every one Hybrid vehicle in service. All else being equal, users most prefer Hybrid vehicles. Users who report driving longer distances prefer not to take either electric vehicles or Plug-in Hybrids, despite the fact that Plug-in Hybrids do not have significant range limitations.